PENERAPAN KONSEP ARSITEKTUR INDUSTRIAL PADA BANGUNAN HOTEL (STUDI KASUS: THE SOMOS HOTEL, KOLOMBIA) (Jurnal Koridor, 2021)
Industrial development in a country usually contributes to its national economy. Tourism as an industrial sector also contributes to increasing foreign exchange for the country. A building that is closely related to the tourism industry is a hotel. In general, hotel buildings use a concept that prioritizes comfort factors, such as: natural colors, cozy, neat, and others. Apart from this habit, some hotels use industrial concepts that prioritize functional and efficient aspects, such as: the use of unfinishing materials and utilities that are left as they are so that it gives the impression of sacrificing the comfort aspects commonly applied to hotel buildings. Therefore, this study aims to find out how to apply industrial concepts that are suitable for hotel buildings. This study uses a qualitative method with a descriptive approach. The study uses a case study on the same building and concept.Â  Because hotels that use this concept are rarely found in Indonesia, the case study used is The Somos Hotel in Colombia. From this research, the conclusion is that the application of industrial concepts cannot be applied to all rooms in the hotel. The industrial concept in hotel buildings uses geometric shapes and firm lines, natural colors and monochrome colors, honesty in the use of materials and exposure to utility systems in public spaces.